Pekalongan, The World’s City of Batik, Embraces Plurality Through Cultural Events with Religious Background - Murti Sri Budiarto, Wisnu; Restiani, Arum Dyah; Evelina, Lidya Wati (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This journal investigates Pekalongan’s city branding through the Giant Lopis tradition and the Ritual & Culture Carnival. As the world’s batik hub, Pekalongan’s cultural richness and diverse communities, epitomized as the Batik City, are integral to its identity. The Giant Lopis tradition, featuring colossal rice cakes, symbolizes unity among diverse ethnic and religious groups, fostering harmony. Conversely, the Ritual & Culture Carnival by Klenteng Po An Thian Pekalongan highlights Chinese cultural expressions, enhancing the city’s cultural tapestry. Using qualitative methods such as ethnographic observations and content analysis, this research explores how these traditions contribute to Pekalongan’s branding as a plural city. Additionally, various cultural backgrounds, including Chinese and Islamic, contribute to the diversity of Batik motifs. Findings underscore their positive impact, fostering resident pride, intercultural bonds, and attracting domestic visitors. This study offers valuable insights for policymakers and marketers aiming to leverage cultural heritage for inclusive city promotion.